Story beats in videogames as value-driven choice-based unit operations - Mochocki, Michał; Koskimaa, Raine (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
We present a framework of story beats, defined as microunits of dramatic action, as a tool for the ludonarrative analysis of videogames. First, we explain the Goal - Action - Reaction - Outcome model of the story beat. Then, we present six types of story beats, Action, Interaction, Inaction, Mental, Emotion, and Sensory, providing videogame examples for each category. In the second half of the paper, we contextualise this framework in the classic game studies theory of videogame narrative and player action: unit operations, gamic action, anatomy of choice, and game design patterns, wrapping it up in the most recent trends in cognitive narratology. Ultimately, we present the story beat as a ludonarrative unit, working simultaneously as a ‘unit operation’ in the study of games as systems, and as a microunit of character action in narrative analysis. The conclusion outlines prospective directions for using story beats in formal, experiential, and cultural game research.